Determinant of Audit Forensic in Indonesia - Rida Perwita Sari; Erna Sulistyowati; Rika Puspita Sari (Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine the influence of determinants on forensic audits, which were conducted on educators and internal auditors in Indonesia. Empirical studies in a quantitative context include statistical analysis in data management. The sampling technique was carried out randomly from the population. Research with survey techniques with the help of questionnaires. Data analysis was carried out by direct and indirect tests with the help of WarpPLS (SEM). The results of this study indicate that communication skills has an effect on forensic auditing, problem solving skills has an effect on forensic auditing, presentation skills has an effect on forensic auditing, forensic accounting curriculum has an effect on forensic auditing, forensic accounting curriculum partially mediates the effect of communication skills on forensic auditing, the forensic accounting curriculum partially mediates the effect of problem solving skills on forensic auditing, and the forensic accounting curriculum does not mediate the effect of presentation skills on forensic auditing. The implications of this research are aimed at the auditor profession in Indonesia so that they pay more attention to their own ability to attend forensic auditor training and have professional certification before taking a forensic audit job.